Which climate-smart agriculture technologies are farmers willing to put their money on? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
CCAFS together with our partner organisations conducted studies on farmers’ preferences and willingness to pay, using priority setting tools developed by the International Food Policy Research Institute (IFPRI). Studies in South Asia explored the potential technological options for climate risk management in various farming systems. They listed the most preferred technologies and/or interventions and assessed farmers’ willingness to pay for them.